Long term follow-up in a patient with a de novo microdeletion of 14q11.2 involving CHD8 - Drábová, Jana; Seemanová, Eva; Hančárová, Miroslava; Kremlíková Pourová, Radka; Horáček, Martin; Jančušková, Tereza; Peková, Soňa; Novotná, Drahuše; Sedláček, Zdeněk (American journal of medical genetics. Part A, 2015)
We identified a de novo deletion of 14q11.2 in a Czech patient with developmental delay, mild autistic features, macrosomy, macrocephaly, orthognathic deformities, and dysmorphic facial features. The clinical follow-up of the patient lasting 14 years documented changes in the facial dysmorphism from infancy to adolescence. The deletion affects approximately 200 kb of DNA with five protein-coding genes and two snoRNA genes. Two of the protein-coding genes, SUPT16H and CHD8, have been proposed as candidate genes for a new microdeletion syndrome. Our patient further supports the existence of this syndrome and extends its phenotypic spectrum, especially points to the possibility that orthognathic deformities may be associated with microdeletions of 14q11.2. CHD8 mutations have been found in patients with neurodevelopmental disorders and macrocephaly. The HNRNPC gene, repeatedly deleted in patients with developmental delay, is another candidate as its 5́ end is adjacent to the deletion, and the expression of this gene may be affected by position effect.
Keywords: chromozomální delece; DNA vazebné proteiny; transkripční faktory; Chromosomes, Human, Pair 14; Adolescent; megalencefalie; lidé; mnohočetné abnormality; Transcription Factors; následné studie; lidské chromozomy, pár 14; Intellectual Disability; Follow-Up Studies; Male; Developmental Disabilities; Chromosome Deletion; vývojové poruchy u dětí; Megalencephaly; DNA-Binding Proteins; Abnormalities, Multiple; mužské pohlaví; mentální retardace; mladiství; Humans